Development of Students’ Learning Outcomes with Learning Activities Package on the Categories of Thai Words Using Flipped Classroom Technique for the 3rd Year Chinese Students - Kosa, Katyada; Thaima , Waraporn (Journal of Modern Learning Development, 2023)
The objectives of this research were to: 1) study the process of developing learning outcomes with learning activities package on the categories of Thai words by using flipped classroom technique for a group of 3rd year Chinese students, and 2) compare the learning outcomes from pre-test and post-test with learning activities package on the categories of Thai words by using flipped classroom technique for the 3rd year Chinese students. Pre-Experimental Research Design. There were 2 sets of research tools used in the research, which were divided into 1. learning management tools, that was a learning management plan with flipped classroom technique with learning activities package, and 2. the data collection tool was the categories of Thai words test. The sample group of this research was 68 3rd year students in the Thai language program from Southwest Forestry University in 1st semester, academic year 2021, and it was obtained by Cluster sampling. The statistics used in data analysis were mean, standard deviation, and t-test (dependent t-test). The results of the study revealed that: 1. The process of developing learning outcomes with learning activities package on the categories of Thai words by using flipped classroom technique for the 3rd year Chinese students produced a 7-asynchronous units combination between a traditional study and self-study and 7-synchronous units in the classroom. Students studied the content on the categories of Thai words from learning activities package which was created by the researcher. There were a pre-test and a post-test to evaluate the students’ achievement on the categories of Thai words before and after studying. 2. The comparison of the learning outcomes from learning activities package on the categories of Thai words by using flipped classroom technique found that the average score of the pre-test was 15.68 and the mean score of the post-test was 33.68. In addition, the students’ post-test scores were significantly higher than the pre-test scores at a level of .05.